2023
DOI: 10.1007/s00244-023-00986-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preschool Children’s Exposure Levels to Organophosphate and Pyrethroid Pesticide: A Human Biomonitoring Study in Two Turkish Provinces

Abstract: Pesticides are products that were developed for the bene t of humanity. However, now they are one of the critical risk factors threatening the environment, and they create a signi cant threat to the environmental health of children. Organophosphate (OP) and pyrethroid (PYR) pesticides are widely used in Turkey as well as all over the world. The main focus of this presented study was to analyze the OP and PYR exposure levels in urine samples obtained from 3-6 year old Turkish preschool children who lives in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In 60% of the studies included in Table , the concentration of pesticides in urine is higher in women. Higher levels, exceeding 30% more, were reported for 3-PBA, DAPs, and TCPY in females. Slightly higher values for specific pesticides, e.g., ETU and glyphosate, , were observed in males.…”
Section: Demographic and Lifestyle Variablesmentioning
confidence: 76%
See 3 more Smart Citations
“…In 60% of the studies included in Table , the concentration of pesticides in urine is higher in women. Higher levels, exceeding 30% more, were reported for 3-PBA, DAPs, and TCPY in females. Slightly higher values for specific pesticides, e.g., ETU and glyphosate, , were observed in males.…”
Section: Demographic and Lifestyle Variablesmentioning
confidence: 76%
“…In 60% of the studies included in Table 8, the concentration of pesticides in urine is higher in women. Higher levels, exceeding 30% more, were reported for 3-PBA, 83 DAPs, 45 and TCPY 42 specific pesticides, e.g., ETU 37 and glyphosate, 61,64 were observed in males. However, in some studies, no correlation was found between urinary levels and gender.…”
Section: Vegetarian Versus Nonvegetarianmentioning
confidence: 81%
See 2 more Smart Citations